Exploring the Impact of Learning Motivation Interactions on Problem Solving Skills in Social Studies Learning - Peggi Pratiwi; Disman Disman; Siti Nurbayani (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
ABSTRACT This study aims to investigate the influence of theThis study aims to investigate the influence of the interaction between learning motivation and problem-solving skills in IPS education at SMP FK Bina Muda Cicalengka. Utilizing a quantitative approach and experimental design with a factorial model of 2^3, this research involved two groups: an experimental group (31 students) and a control group (32 students). Data collection methods included observation, documentation, IPS tests (Pretest and Posttest), and questionnaires. Data analysis was conducted using descriptive statistics and inferential statistics with multivariate analysis methods using One-Way ANOVA tests and supported by SPSS 26.0 software. The research findings indicate a significant improvement in problem-solving skills in the experimental group using Problem-Based Learning (PBL) compared to the control group using Project-Based Learning (PjBL), particularly in the context of learning motivation interaction. Descriptive statistics show a higher average normalized improvement score in the experimental group (0.8424) compared to the control group (0.7092), demonstrating the superior efficacy of Problem-Based Learning (PBL) in enhancing problem-solving skills. The comparison of One-Way ANOVA tests for Problem-Based Learning and Project-Based Learning in enhancing students' problem-solving skills shows significant differences. The One-Way ANOVA test results for PBL indicate (Frequency=42.232, sig<0.000). On the other hand, the One-Way ANOVA test for PjBL shows (Frequency=4.911, sig<0.014). This suggests that both PBL and PjBL have significant impacts on improving students' problem-solving skills, but the effects vary depending on students' learning motivation levels. Furthermore, the interaction effect test shows results (Frequency = 4.415, sig= 0.016<0.05), indicating an interaction effect between PBL and PjBL influenced by learning motivation levels. This emphasizes the efficacy of PBL in engaging learners and improving problem-solving skills, as well as the importance of considering teaching methods and students' motivational factors in lesson planning.Keywords: Interaction of learning motivation, problem-solving skills, Social Studies, experimental approach, factorial design.